PEMANFAATAN SUMBER BELAJAR DIGITAL TERHADP PENGEMBANGAN PESERTA DIDIK DI SDN 13 MUARA SIBERUT PADA ERA REVOLUSI 4.0 - Suhendra, Irwan; Putri, Riska Nanda; Darmansyah, Darmansyah; Fitria, Yanti (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The rapid development of science and technology has a significant impact on human life, especially in the context of education. Digital technology brings great convenience and innovation. Services become faster, more efficient and have a wide range of connections both online and offline. Although it provides benefits in everyday life, the use of digital technology in the context of education also brings negative impacts. The education sector continues to follow the development of science and technology, especially in the industrial revolution 4.0, with a focus on information and communication technology. Education must learn and adapt to these changes, and educators are expected to apply them to help learners solve learning problems and improve their performance. In this context, significant performance improvement occurs in the education sector, especially for teachers, who have a crucial role in changing learning approaches and improving the quality of education. The result of this study is that most teachers at SDN 13 Muara Siberut cannot utilize these digital learning resources, because they cannot apply or use digital learning resources, therefore it is necessary to increase the competence of teachers by holding workshops, training or upskilling.